Landscape design for gully erosion control on the upper slopes of Mount Sumbing, Central Java, Indonesia - Maulana, Edwin; Sartohadi, Junun; Setiawan, Muhammad Anggri (Brawijaya University, 2025)
Gully erosion can cause significant soil loss; thus, it must be controlled. This study aimed to develop a landscape design for controlling gully erosion in a volcanic environment with a thin soil layer. The primary data used was Unmanned Aerial Vehicle (UAV) data combined with field surveys and in-depth interviews. A collaborative approach was used to develop the landscape design to minimize the impact of gully erosion. The finding showed that gully erosion had entered adult to old age since the scars (incisions) at the gully bottom existed. According to the community, gullies must be controlled, although they do not affect land productivity. Vegetative control is the most favored method of gully erosion control. Local vegetation with the potential for additional value is chosen to control gully erosion. Strengthening community capacity is the most favorable way to manage gullies. Through good understanding, local communities can control the development of gullies. Further strengthening of regulations related to gully erosion control will have a domino effect on land sustainability. This finding can be extrapolated globally to locations with similar land characteristics.